2002
DOI: 10.1038/sj.eye.6700027
|View full text |Cite
|
Sign up to set email alerts
|

Non-trachomatous corneal opacities in the Gambia—aetiology and visual burden

Abstract: Aims National blindness surveys conducted in the Gambia in 1986 and 1996 showed an increase in blindness and visual impairment from non-trachomatous opacity. This study aimed to investigate the aetiology of these opacities and to assess the resulting visual burden. Methods A population-based, randomised blindness survey was conducted in the Gambia in 1996. Patients with visual impairment or blindness were examined by an ophthalmologist with a slit lamp. Causes of corneal opacity were determined as accurately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
(14 reference statements)
0
10
2
Order By: Relevance
“…In Thailand, these were infections (35.6%), surgical bullous keratopathy (27.8%), and trauma (14%) 19. In Gambia, vitamin A deficiency (7.8%) was an important cause of corneal blindness in addition to infectious keratitis (22.7%) and trauma (14.3%) 20. Thus, contrary to popular belief and previous studies,17 19 20 the predominant cause of corneal blindness in the current study was not infectious keratitis but corneal decompensation following cataract surgery.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In Thailand, these were infections (35.6%), surgical bullous keratopathy (27.8%), and trauma (14%) 19. In Gambia, vitamin A deficiency (7.8%) was an important cause of corneal blindness in addition to infectious keratitis (22.7%) and trauma (14.3%) 20. Thus, contrary to popular belief and previous studies,17 19 20 the predominant cause of corneal blindness in the current study was not infectious keratitis but corneal decompensation following cataract surgery.…”
Section: Discussioncontrasting
confidence: 69%
“…In Gambia, vitamin A deficiency (7.8%) was an important cause of corneal blindness in addition to infectious keratitis (22.7%) and trauma (14.3%) 20. Thus, contrary to popular belief and previous studies,17 19 20 the predominant cause of corneal blindness in the current study was not infectious keratitis but corneal decompensation following cataract surgery. Addressing the issue of improving the quality of cataract surgical services in the country will help reduce the requirement for corneal transplantation.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…1 As trachoma and vitamin A deficiency become less common, suppurative keratitis is becoming the major cause of corneal blindness in the developing world. 13 While contact lens use is a major risk factor for corneal ulceration in the developed world, a high prevalence of fungal infections, agriculture related trauma, and use of traditional eye medicines is unique to the developing world. 14 15 A significant percentage of patients with microbial keratitis referred to our tertiary hospital are at a stage of impending or established corneal perforation.…”
mentioning
confidence: 99%
“…Corneal opacities vary greatly in extent and location and are usually associated with other anomalies [17], for example the bilateral congenital choanal atresia and congenital right accessory nasal deformity in our patient. Because corneal opacity is a cause of blindness [18], timely treatment is crucial. A study has shown that 64.92% of patients underwent cosmetic treatment after the primary visit [16].…”
Section: Discussionmentioning
confidence: 99%